Atrial fibrillation in critical illness: state of the art - Sibley, Stephanie; Bedford, Jonathan; Wetterslev, Mik; Johnston, Brian; Garside, Tessa; Kanji, Salmaan; Whitehouse, Tony; Welters, Ingeborg; Ostermann, Marlies; Balik, Martin; Lancini, Daniel; Dharmaraj, Blossom; et al. (Intensive care medicine, 2025)
Atrial fibrillation (AF) is the most common arrhythmia experienced by critically ill patients. It has been associated with adverse short-and long-term outcomes, including an increased risk of thromboembolic events, heart failure, and death. Due to complex and multifactorial pathophysiology, a heterogenous patient population, and a lack of clinical tools for risk stratification validated in this population, AF in critical illness is challenging to predict, prevent, and manage. Personalized management strategies that consider patient factors such as underlying cardiac structure and function, potentially reversible arrhythmogenic triggers, and risk for complications of AF are needed. Furthermore, evaluation of the effects of these interventions on long-term outcomes is warranted. Critical illness survivors who have had AF represent a unique population who require systematic follow-up after discharge. However, the frequency, type, and intensity of follow-up is unknown. This state-of-the-art review aims to summarize the evidence, contextualize the current guidelines within the setting of critical illness, and highlight gaps in knowledge and research opportunities to further our understanding of this arrhythmia and improve patient outcomes.
Keywords: Risk Assessment; rizikové faktory; hodnocení rizik; Humans; Critical Illness; kritický stav; Risk Factors; Atrial Fibrillation; fibrilace síní; Critical illness; lidé; Atrial fibrillation